Tarian Kataga Pada Masyarakat Wanokaka Di Desa Tara Manu Kecamatan Wanokaka Kabupaten Sumba Barat - Meti, Lusia Leka; Tosi, Esry D. (Universitas Nusa Cendana, 2022)
The Kataga dance is usually performed during traditional festivals such as harvest thanksgiving accompanied by gongs and traditional songs. Currently, some people no longer use the Kataga dance in traditional parties, but tend to use modern music. The formulation of the problem in this research is what is the history and existence of the Kataga Dance and what values ​​are contained in the Kataga Dance in the Wanokaka Community. The research method used is a qualitative method. The primary data sources are traditional leaders and community leaders, while the secondary data sources are libraries in the form of books, brochures, and so on. Data collection uses interview and observation techniques. The research results show that the history of the formation of the Kataga dance is that in inter-tribal wars in Sumba, the winning party had the right to take the enemy's head home and hang it in the Adung (courtyard). Kataga in modern times is rarely performed at harvest thanksgiving events or entering a new house but has shifted to modern music. The values ​​contained in the Kataga dance are the values ​​of solidarity, culture, history and spirit.